2017
DOI: 10.1016/j.biochi.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous ligand selectivity of the H-NOX sensor protein from Shewanella oneidensis and comparison to those of other bacterial H-NOXs and soluble guanylyl cyclase

Abstract: To delineate the commonalities and differences in gaseous ligand discrimination among the heme-based sensors with Heme Nitric oxide/OXygen binding protein (H-NOX) scaffold, the binding kinetic parameters for gaseous ligands NO, CO, and O2, including KD, kon, and koff, of Shewanella oneidensis H-NOX (So H-NOX) were characterized in detail in this study and compared to those of previously characterized H-NOXs from Clostridium botulinum (Cb H-NOX), Nostoc sp. (Ns H-NOX), Thermoanaerobacter tengcongensis (Tt H-NOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
(110 reference statements)
0
20
0
Order By: Relevance
“…This 6‐coordinate complex then converts to a 5‐coordinate ferrous nitrosyl complex as the strong‐field NO ligand induces the cleavage of the Fe II ‐His bond . It has been observed that the rate of conversion of the 6‐coordinate intermediate to the final 5‐coordinate complex is dependent on the concentration of NO (Figure A, k 2 ). The NO dependence of this transformation was rationalized by invoking the formation of a dinitrosyl intermediate, which could form either a proximal or distal 5‐coordinate complex by dissociation of the opposite NO molecule.…”
Section: Mechanism Of No Association/dissociationmentioning
confidence: 99%
“…This 6‐coordinate complex then converts to a 5‐coordinate ferrous nitrosyl complex as the strong‐field NO ligand induces the cleavage of the Fe II ‐His bond . It has been observed that the rate of conversion of the 6‐coordinate intermediate to the final 5‐coordinate complex is dependent on the concentration of NO (Figure A, k 2 ). The NO dependence of this transformation was rationalized by invoking the formation of a dinitrosyl intermediate, which could form either a proximal or distal 5‐coordinate complex by dissociation of the opposite NO molecule.…”
Section: Mechanism Of No Association/dissociationmentioning
confidence: 99%
“…VAL77, ILE78, SER81, TYR82, VAL107 and TYR111 see Figure 4 ) leading to one side of the heme group. For this system, the direct Tunnel 2 , previously suggested to be universal for all H-NOXs, was not observed [ 9 ]. Closer inspection showed that this tunnel is blocked at both ends in Ka .…”
Section: Resultsmentioning
confidence: 78%
“…Both of these routes are short and provide easy access to both the distal and the proximal sides of the heme. These tunnels may play a major role in the reactivity of sGC [ 36 ], Shewanella oneidensis ( So ) H-NOX [ 9 ] and Vibrio cholera ( Vc ) H-NOX for which ligand-binding to the proximal side has also been suggested. Tunnel 1 , the long apolar tunnel has been visited by ligands at its entrance towards the solvent phase; however, the exit to the distal pocket remained fully blocked by a hydrogen bonding triad (TYR140 with sidechains of TRP9 and ASN74).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations